2019
DOI: 10.1001/jamaneurol.2019.3063
|View full text |Cite|
|
Sign up to set email alerts
|

Rate and Prognosis of Brain Ischemia in Patients With Lower-Risk Transient or Persistent Minor Neurologic Events

Abstract: for the Diagnosis of Uncertain-Origin Benign Transient Neurological Symptoms (DOUBT) Study Group IMPORTANCE Early treatment of patients with transient ischemic attack (TIA) reduces the risk of stroke. However, many patients present with symptoms that have an uncertain diagnosis. Patients with motor, speech, or prolonged symptoms are at the highest risk for recurrent stroke and the most likely to undergo comprehensive investigations. Lower-risk patients are much more likely to be cursorily investigated.OBJECTIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 25 publications
3
70
0
2
Order By: Relevance
“…Various recent studies have shown a poorer prognosis of tissue-positive events compared to that of tissue-negative events, thus contributing to the transition from time-based to tissue-based definitions of AIS and TIA [ 1 , 9 , 11 , 31 , 32 ]. Similarly, we have demonstrated that the positive conversion of DWI lesions is also associated with a higher risk of vascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Various recent studies have shown a poorer prognosis of tissue-positive events compared to that of tissue-negative events, thus contributing to the transition from time-based to tissue-based definitions of AIS and TIA [ 1 , 9 , 11 , 31 , 32 ]. Similarly, we have demonstrated that the positive conversion of DWI lesions is also associated with a higher risk of vascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities detected on MRI can be very useful in diagnosis, especially when symptoms are transient, and can be very useful in determining whether the aetiology was ischaemic. The presence of MRI-defined ischaemic lesions in addition to confirmation of diagnosis is associated with a significantly higher risk of future stroke risk [ 17 ]. MRI is however not necessary in the assessment of most stroke mimic patients as the clinical examination and the CT imaging is sufficient to make a firm diagnosis.…”
Section: Assessment Of the Patient With Suspected Acute Strokementioning
confidence: 99%
“…Although there are few publications and no widely accepted definition for TIA mimics [29,30], our study and other reports suggest that more than 50% of patients who are referred to TIA clinics are in fact TIA mimics [6,7,31]. Given a high estimated incidence rate of TIA in the United States, a high rate of misdiagnosis can be associated with significant cost burden and missed opportunities [32][33][34]. Misdiagnosing patients that are experiencing TIA carries significant costs for both the hospital and the patient [6].…”
Section: Discussionmentioning
confidence: 65%